Optimisation of CaCl2 impregnated expanded graphite and alginate matrices – Targeted salt loading - Jack Reynolds (Energy Conversion and Management, 2024)
The incorporation of salt hydrates in thermochemical energy storage is often limited by poor kinetics and mechanical instability during charge and discharge cycles. This study explores the influence of salt loading on the energy storage capacity and charge/discharge performance of salt-impregnated expanded graphite and alginate composites. By controlling the salt bath concentration during composite synthesis, the quantity of salt within the bead can be regulated. Four composites have been synthesised with salt wt% values ranging from 63.7 to 77.2 %, resulting in salt volumetric densities form 0.22–0.52 g/cm3 and energy densities between 1052 and 1281 kJ/kg. The study found that increasing salt bath concentration above 60 % significantly decreases the porosity within the composite. This reduces moisture transfer kinetics and also fails to accommodate for salt expansion and deliquescence. Consequently, composites at near-maximum salt capacity displayed diminished discharge performance and charge efficiency. Conversely, samples below the saturation threshold exhibited greater heat output and charge efficiency, contained overhydration, and maintained structural integrity. These findings highlight the importance of carefully balancing energy storage capacity with improved reaction kinetics and stability to achieve an optimal storage solution in solar thermal systems or waste heat recovery.